Integrasi Pendidikan Anti Narkoba dalam Pendidikan Agama Islam dan Budi Pekerti Kurikulum 2013 - Machali, Imam (Nadwa, 2014)
This article describe the antidrug education and the integration of anti-drug education in the curriculum of Islamic religious and moral education of the year 2013. The results showed that the antidrug education began in elementary, jun-ior and senior high school that includes knowledge about drugs and the dangers, increase self-esteem, and the formation of assertiveness. Integration of anti-drug education in the curriculum of Islamic religious education and moral includes three aspects, namely: knowledge (cognitive), attitudes and behaviours (affec-tive), and skills (psychomotor). Implementation of antidrug education at school level using integrative-inclusive strategy. Anti-drug education learning man-agement can be integrated in all subjects, both religious and secular.Â Abstrak Artikel ini bertujuan mendeskripsikan pendidikan anti narkoba dan integrasi pendidikan anti narkoba pada kurikulum Pendidikan Agama Islam dan Budi Pekerti Tahun 2013. Hasil penelitian menunjukkan bahwa pendidikan antinarkoba sudah dimulai sejak SD, SMP dan SMA yang mencakup pengetahuan tentang narkoba dan bahayanya, peningkatan harga diri, dan pembentukan asertasi. Integrasi pendidikan anti narkoba pada kurikulum Pendidikan Agama Islam dan Budi Pekerti mencakup tiga domain, yakni domain pengetahuan (kognitif), sikap dan perilaku (afeksi), dan keterampilan (psikomotorik). Implementasi pendidikan antinarkoba di jenjang sekolah menggunakan strategi integratif-inklusif. Manajemen pembelajaran pendidikan antinarkoba dapat diintegrasikan di semua mata pelajaran, baik agama maupun umum.